Development of heat resistant Pb-free joints by TLPS process of Ag and Sn-Bi-Ag alloy powders - Ohnuma I.; Kainuma R.; Ishida K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
TLPS (Transient Liquid Phase Sintering) process is a candidate method of heat-resistant bonding, which makes use of the reaction between low-melting temperature powder of Sn-Bi base alloys and reactive powder of Ag. During heat treatment above the melting temperature of a Sn-Bi base alloy, the molten Sn-Bi reacts rapidly with solid Ag particles, which results in the formation of heat-resistant intermetallic compound (IMC). In this study, the TLPS properties between Sn-17Bi-1Ag (at.%) powder with its liquidus temperature of 200°C and pure Ag powder were investigated. During differential scanning calorimetry (DSC) measurement, an exothermic reaction and an endothermic reaction occurred, which correspond to the formation of the e-Ag3Sn IMC phase and the melting of the Sn-17Bi-1Ag alloy, respectively. After the overall measurement, the obtained reactant consists of the Ag3Sn-IMC and Bi-rich phases, both of which start melting above 250°C, with a small amount of the residual Sn-Bi eutectic phase. These results suggest that the TLPS process can be applied for Pb-free heatresistant bonding.